Enhancing Narrative Text Reading Comprehension Through Augmented Reality-Assisted Pop-Up Book Media Development - Dwi Sukma Wijayanti; Nugraheti Sismulyasih Sb; Panca Dewi Purwati (STAI Hubbulwathan Duri, 2025)
The limited variety of learning media in Grade IV Indonesian language lessons, particularly in local content on narrative texts, has led to low student interest and poor reading comprehension. To address this issue, this study developed and evaluated a Pop-Up Book learning medium enhanced with Augmented Reality (AR). This research involved Grade IV teachers, students, and expert reviewers. Data were collected through observations, interviews, tests, and questionnaires. The primary instruments were questionnaire sheets, while data were analyzed using both qualitative and quantitative descriptive techniques. Effectiveness was measured through pretest–posttest comparisons and N-gain analysis on small- and large-scale trials. Feasibility assessments yielded high scores: material experts (96.66%), media experts (98.75%), teacher responses (97.5%), and student responses (97.08%). Pretest–posttest results showed improved knowledge competence, with N-gain scores of 0.79 (small scale) and 0.66 (large scale), indicating the media was “quite effective” in enhancing reading comprehension. The integration of Pop-Up Books with AR technology provided interactive, visually engaging content that stimulated student interest and facilitated comprehension. The consistently high ratings from experts, teachers, and students confirm its quality and relevance to classroom needs. The AR-assisted Pop-Up Book is highly feasible, effective, and suitable for improving narrative text reading comprehension in Grade IV Indonesian language lessons. Its implementation can serve as an innovative approach to enhance learning engagement and outcomes.